(untitled) (Alternautas, 2023)
In The Urban Enigma: Time, Autonomy, and Postcolonial Transformation in Latin America, Simone Vegliò discusses some dilemmas in forming a post-colonial Latin American urban space based on three major architectural projects in Buenos Aires, Mexico City, and Brasília. The book discusses the projects’ ambitions in line with the vision of modernity at their time while contrasting their aims with the demands of social inclusion, justice, and the continuation of colonial ideas.